Analysis of Guru Penggerak Program: Teacher Satisfaction and Method Implementation Across Different Demographics - Gusti, Valeria Yekti Kwasaning; Kandaga, Thesa; Nurhayati, Suci; Risnawati, Erna (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
This study evaluates the impact of the "Guru Penggerak" program on teaching practices and participant satisfaction, focusing on educators from 36 cities across Indonesia. The program “Guru Penggerak”, initiated by the Indonesian Ministry of Education, empowers teachers to become leaders in educational transformation. It enhances pedagogical skills, leadership abilities, and the integration of local wisdom with global knowledge to develop reflective and innovative educators. This research examines the relationship between satisfaction levels and demographic factors—age, gender, and teaching experience—as well as the frequency of implementing learned methods. Participants (N = 119), predominantly female and experienced educators, rated program aspects, including content relevance, instructional quality, and overall satisfaction, using a Likert scale. Mean ratings ranged from 4.0 to 4.2, indicating a positive reception. Pearson correlation analysis assessed relationships between demographic factors, satisfaction, and implementation frequency. Results showed minimal correlations (age: r = -0.115, gender: r = -0.059, teaching experience: r = -0.006) for satisfaction and weak correlations (age: r = 0.066, gender: r = -0.062, teaching experience: r = 0.127) for implementation frequency, suggesting demographic factors had little influence. Findings indicate the program is well-received across diverse demographics, reinforcing its broad effectiveness. Future research should incorporate qualitative methods to explore additional factors, such as school infrastructure and individual teaching styles, that may influence satisfaction and practical application. Identifying these factors will contribute to optimizing teacher development programs and enhancing their impact on Indonesia’s education system.